2022
DOI: 10.18240/ijo.2022.06.03
|View full text |Cite
|
Sign up to set email alerts
|

Procollagen C-proteinase enhancer 1 promotes physiologic retinal angiogenesis via regulating the process of collagen

Abstract: AIM: To investigate the role of procollagen C-proteinase enhancer 1 (PCPE1) in retinal angiogenesis and relevant mechanisms. METHODS: The Pcolce1-knockout (KO) mice were used to explore the effect of PCPE1 on retinal angiogenesis in vivo. Pcolce1 siRNA were designed, cell count kit 8 (CCK8) assays and tube formation assays were performed to investigate the cell proliferation and tube formation abilities of retinal microvascular endothelial cells (hRMECs) in vitro. Mouse embryo fibroblasts (MEF) cells were isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The mechanism of retinal angiogenesis is very complex, and retinal neovascularization plays a crucial role in the pathological progression of diabetic eye disease. However, there is a lack of relevant research [8,[16][17] . Many studies have shown that there is a close relationship between HDAC functions and diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of retinal angiogenesis is very complex, and retinal neovascularization plays a crucial role in the pathological progression of diabetic eye disease. However, there is a lack of relevant research [8,[16][17] . Many studies have shown that there is a close relationship between HDAC functions and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Int J Ophthalmol, Vol. 16 Histone deacetylases (HDACs) plays a crucial role in regulating the development of various retinal cells, including retinal progenitor cells, photoreceptors, bipolar cells, ganglion cells and Müller glial cells [11] . HDACs IIa (HDAC4/5/7/9) regulate many aspects of cell biology, including proliferation, differentiation, autophagy, apoptosis, migration and angiogenesis [12][13] .…”
Section: Introductionmentioning
confidence: 99%